Prevalence of and factors associated with enamel fracture and other traumas in Brazilian children 8-10 years old - Fernanda Bartolomeo FREIRE-MAIA; Sheyla Márcia AUAD; Mauro Henrique Nogueira Guimarães de ABREU; Fernanda SARDENBERG; Milene Torres MARTINS; Saul Martins PAIVA; Isabela Almeida PORDEUS; Miriam Pimenta VALE (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract The aim of this study was to assess the prevalence and discriminate the associated factors between enamel fractures and other trauma/trauma sequelae in 8 to 10-year-old Brazilian schoolchildren. A representative sample of 1,201 children from public and private schools were enrolled in this cross-sectional study. Questionnaires about sociodemographic characteristics were answered by parents. The outcome variable (traumatic dental injury, TDI) was multi-categorized. Independent individual variables were sex, age, number of residents in household, parents/caregivers' level of education, family income, dental caries, and overjet. Type of school was considered an independent contextual variable. Multilevel analysis, bivariate, and multivariate multinomial logistic regression models were performed. The prevalence of TDI was 14.0% (2.8% with other trauma/trauma sequelae). The multilevel analysis revealed no significant difference between the type of school and TDI. The multinomial logistic regression showed that boys (OR = 2.3; 95%CI: 1.1-4.8), older children (OR = 1.8; 95%CI: 1.1-3.0) and individuals with an overjet > 3 mm (OR = 2.5; 95%CI: 1.0-6.2) were more likely to present other trauma/trauma sequelae. Enamel fracture was not significantly associated with any variables. The prevalence of TDI in 8 to 10-year-old schoolchildren was 14% but only 2.8% of other trauma/trauma sequelae. Differences regarding the associated factors of TDI involving enamel fracture or other trauma/trauma sequelae were detected, suggesting that the different TDI classification cannot be evaluated as a single category.